RANCANG BANGUN SISTEM INFORMASI AKADEMIK BERBASIS WEBSITE MENGGUNAKAN FRAMEWORK LARAVEL 10 STUDI KASUS SEKOLAH TINGGI ILMU KOMPUTER EL RAHMA - Muhammad Sandy Putra Riyadi; Subhan Munafis; Helmi Yoga (Sekolah Tinggi Ilmu Komputer El Rahma, 2026)
In the current digital transformation era, the need for an efficient and integrated academic information system is very important for higher education institutions. El Rahma College of Computer Science faces challenges in managing complex and diverse academic data, such as student data, lecture schedules, attendance and assessments. Therefore, this research aims to design and build a website-based Academic Information System using the Laravel 10 framework. This research method uses the Research and Development method or research and development research. Data collection methods used in this research include observation, interviews and literature study. The system development methods used in this research include the systems approach method, system documentation model. The system approach method used is Object-Oriented Programming (OOP), while the system documentation model uses the Unified Modeling Language (UML) method which consists of various models such as use case diagrams, class diagrams and activity diagrams. The research results show that the system developed has succeeded in increasing the efficiency of academic data management, making information access easier for students and lecturers, and providing the features needed by admins for effective data management. This system is expected to be a reliable and sustainable solution to support the academic process at the El Rahma College of Computer Science.